Medical Imaging: The Missing Element of National Health Plans - Devanshi R. Shah; Leslie Abimbola; Kristen Destigter; Eline van de Broek-Altenburg; Susan Horton; Bernice Dahn (Journal of Global Radiology, 2021)
Purpose: Access to diagnostics is vital for clinical decision-making but is rarely prioritized in national health services strategic plans (NHSSPs)[1].